Determination of carbofuran and diuron in FIA system using electrochemical sensor modified with organometallic complexes and graphene oxide - Wong, Ademar [UNESP]; Taboada Sotomayor, Maria Del Pilar [UNESP] (Elsevier B.V., 2014)
This paper describes the development of an electrochemical sensor coupled to flow injection analysis system for the detection of pesticides. The proposed sensor was prepared using a carbon paste electrode modified with hemin and nickel (II) 1,48,11,15,18,22,25-octabutoxy-29H, 31H-phthalocyanine complex as possible catalysts P450 enzyme and graphene oxide in order to improve the sensitivity of the sensor. In the first place, we used the cyclic voltammetry in a response range of -0.2 to 1 V to monitor the electrochemical response of each pesticide. In optimized conditions, an amperometric study of the proposed sensor was conducted applying the potential of 0.45 and 0.8 V for the redox reaction of carbofuran-phenol and diuron. The system showed a linear response in a concentration range between 5.0 x 10(-6) and 1.4 x 10(-4) and 5.0 x 10(-5) and 1.0 x 10(-3) mol L-1 and detection limit of 1.7 x 10(-6) and 2.0 x 10(-5) mol L-1 for carbofuran and diuron, respectively. The proposed sensor was applied in soil and carrot samples and the results obtained in the recovery study were close to 100%. The reliability of the proposed sensor was confirmed after comparing the results with those obtained in the comparative method (HPLC). (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Pesticides; Organometallic compounds; Graphene oxide; Electrochemical sensor; FIA